(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract : Education has great importance in bringing up generation. The Holy Qur’an represents the proper and clear approach which forms the straight way to educate the individual since it contains educational values that purify the soul. The one who looks at Al-Zuhaili’s interpretation of the Holy Qur’an in Al-Tafsir Al-Munir finds that Al-Zuhaili adhered to a path: one he followed from the first Ayah he interpreted to the last ayah in the Holy Book of God, and he indicated his method in the introduction. Al-Munir’s interpretation of Wahba Al-Zuhaili included many educational issues: at the beginning of his interpretation he talked about some necessary knowledge related to the Qur’an, and he proceeded to complete extrapolation and careful, careful study in which he dealt with contemporary issues, including social, political, and jurisprudential ones. In this research, we will discuss some of these issues related to educational issues This paper covers four topics: the definition of educational implications ; definition of Wahba al-Zuhaili and his exegetical approach; the educational implications of the verses of doctrine(Ayat al-Aqeedah); the educational implications of the verses of constrains, and finally the educational implications of the verses of ethics(Ayat al akhlaq) a conclusion and references.